Titan - The life of John D Rockefeller, Sr. - Chernow, Ron (New York Random House, 1998)
A biography of America's first billionaire, John D. Rockefeller, Sr., drawing from Rockefeller's personal papers to provide information about his rustic origins, his creation of Standard Oil, his often controversial business tactics, and his personal relationships and attributes
d unk
Keywords: Rockefeller, John D., Sr. -- biography; Capitalists and financiers -- Biography; Exxon Corporation -- Biography; Industrialists -- Biography